Biodiesel e agricultura familiar no Tocantins: uma análise a partir da teoria dos conjuntos Fuzzy - Ribeiro, Vinícius Souza (Universidade Federal do Tocantins, 2016)
The need for diversification of energy sources has accelerated the search for renewable sources, in the face of fossil fuel depletion. In this panorama, the Brazilian government launched the National Plan for Production and Use of Biodiesel (PNPB), with the aim of introducing an adherent biofuel to climatic conditions of the country and it had as a principle of social inclusion of family agriculture and regional development. In this context, the aim of this study is to evaluate the effectiveness of PNPB as to its goal of inclusion of the poorest farmers in the biodiesel production chain of Tocantins, as well as if the production of soybeans for bioenergy purposes generates higher income to family farmers compared to the traditional family plantings income in Brazil, and identify and assess the environmental impacts and impacts on food security from the cultivation of soybeans. Were used primary data through questionnaires, along with 30 soybean producing families and 32 non-producing families of oilseeds, located in 9 counties in the Central Tocantins, where through quantitative and qualitative data was drawn an indicator of multidimensional poverty to families, from the theory of fuzzy sets in turn used to estimate via probit econometric model, the probability of relatively poorer families make part of the Tocantins biodiesel production chain. The results showed that the PNPB was not able to include the poorest families in the bioiesel supply chain, and reduced the odds of these families are included, and that the determinants of this exclusion are reflective of weakness of producing soy biodiesel in an environment where there not a consolidated soybean complex. Moreover the soybean was not able to generate higher income than traditional crops, especially given the productive losses suffered by farmers, caused by late planting of soybeans, result of the slow release of funding for the 2011/2012 season. Regarding the environmental impacts, despite the cultivation of soybeans have adverse impacts already expected on the Cerrado biome, the pattern of change in land use adopted by households was able to mitigate such expected effects. The results also indicated, in dimensions of access and availability of food, that the adoption of soybean did not affect the levels of food security of the families surveyed. Finally, this study concluded that PNPB is not a effective public policy that contributes to inclusion, since it does not enter the production chain the relatively poorer farmers and eventually excluded from society and that particularly require greater opportunities to be socially included.